Comparison of the Effectiveness of Using Cinnamon Decoction and Carrot Juice on Lowering Blood Glucose Levels in Patients with Type 2 Diabetes Milatus at Proclamation Hospital - Tri Mochartini; Irna Hartini (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Diabetes mellitus is a metabolic disorder characterized by an increase in blood glucose levels due to impaired insulin secretion. Blood glucose control in addition to pharmacological therapy can be done through non-pharmacological therapy using cinnamon decoction and carrot juice where it is known that cinnamon and carrots have active ingredients that can lower blood glucose levels.Research Objective: Tofind out the comparison of the effectiveness of the use of cinnamon decoction and carrot juice on the reduction of blood glucose levels in patients with type 2 Diabetes Mellitus at Proclamation Hospital.Research Method: This study uses quantitative research with a quasi-experimental research design with a pre-test post-test control group design. The sample of 72 respondents with type 2 diabetes mellitus was grouped into 2, namely the cinnamon decoction intervention group and the carrot juice intervention group carried out for 5 days. The statistical test used is a paired t-test using the SPSS 25 statistical program. Study Results: The results of bivariate analysis using the paired t-test with a sample of 72 respondents (N=72) 36 respondents of the cinnamon decoction intervention group obtained a pre-test mean of 218.83 mg/dL and a post-test of 197.19 mg/dL and a p-Value (0.000) and 36 respondents of the carrot juice intervention group obtained a pret-test mean of 208.44 mg/dL and a post-test of 190.16 mg/dL and a p-Value value (0.000).Conclusion and Recommendation: Cinnamon decoction and carrot juice are equally effective in lowering blood glucose levels in patients with type 2 diabetes mellitus.